Assessing efficiency in the pharmaceutical sector of Nigeria - Efayena Oba Obukohwo; Enoh H. Olele; Patricia N. Buzugbe (CBN Journal of Applied Statistics, 2018)
The study analyses, empirically, the efficiency of the Pharmaceutical sector in Nigeria. Employing a balanced panel of 20 pharmaceutical firms between 2012 and 2016, the paper uses a non-parametric technique (Data Envelopment Analysis) to analyze the firms' efficiency under the constant returns to scale (CRS) and variable returns to scale (VRS) assumptions. The results obtained shows inefficiency in the pharmaceutical sector as it operates under a decreasing return to scale. This calls for an appropriate policy mix to stimulate the efficiency of the pharmaceutical sector in Nigeria by enhancing research and development (R&D) as ell as regulations within the sector.
Keywords: D1; L1; 330; Data Envelopment Analysis; Efficiency; Firm; Performance; Pharmaceuticals